2013
DOI: 10.1080/10413200.2012.718313
|View full text |Cite
|
Sign up to set email alerts
|

Revs and Psychos: Role, Impact and Interaction of Sport Chaplains and Sport Psychologists within English Premiership Soccer

Abstract: Despite an increased focus on spirituality and athlete well-being in sport (Watson, 2011), there is limited research regarding those who provide support to the athlete in these areas. The aim of this study was to explore the practice of sport psychologists and sport chaplains within professional soccer, and identify potential for working partnerships. By interviewing three psychologists and four chaplains who are employed currently within English Premiership soccer, it was revealed that significant overlap in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…This helps to build trust and to overcome potential barriers between staff and players. In English professional football the sports chaplain is often seen as a key provider of help and support for those experiencing adversity and as someone who players and staff respect in terms of trust and integrity (Gamble, Hill & Parker, 2013;Nesti, 2010).…”
Section: Football Youth and The Epppmentioning
confidence: 99%
See 3 more Smart Citations
“…This helps to build trust and to overcome potential barriers between staff and players. In English professional football the sports chaplain is often seen as a key provider of help and support for those experiencing adversity and as someone who players and staff respect in terms of trust and integrity (Gamble, Hill & Parker, 2013;Nesti, 2010).…”
Section: Football Youth and The Epppmentioning
confidence: 99%
“…More recent research has suggested that there is a degree of overlap between the role of the sports chaplain and that of the sport psychologist, the former being viewed as someone who is primarily interested in the well-being of the person, the latter as being primarily concerned with the enhancement of player performance (Nesti, 2010). Gamble et al (2013) observe that the sport psychologist and the sports chaplain bear similarities in their roles particularly concerning pastoral care, but that sports chaplains can also offer spiritual support which may facilitate discussion around specific faith issues as well as enhancing player contentment.…”
Section: Football Chaplaincy and Holistic Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Sport has been explored not only by philosophers, sociologists, or psychologists but also by theologians, priests, and religious leaders (Parker & Weir, 2012). The role of sport chaplaincy is increasingly visible (Dzikus, Waller, & Hardin, 2011;Gamble, Hill, & Parker, 2013). The theme of religion and spirituality in human movement activities opens a currently expanding ideological space, which calls for deeper reflection.…”
Section: Introductionmentioning
confidence: 99%